Cyclone microbubble flotation for enhanced oil recovery from palm oil mill effluent - Van Tuan, Le (Hue University Journal of Science: Natural Science, 2025)
In this study, we investigate cyclone microbubble (CMB) flotation for oil recovery from palm oil mill effluent (POME) under batch and continuous operations. Designed to reduce floated waste and enhance oil separation, the process was tested on a real POME from a Malaysian palm oil mill, with high temperature, low pH, and fluctuating oil and grease (O&G), total solids (TS), and chemical oxygen demand (COD) levels. For a mill processing 1,000 tons of fresh fruit bunches (FFB) daily, the POME discharge contained 7.9 tons of O&G, 36.5 tons of TS, and 59.2 tons of COD. Batch flotation achieved ~63.8% of O&G separation with a 60-minute retention time, whereas continuous flotation (flow rate > 20 L/min) showed a lower efficiency (36 ± 9%). However, O&G was enriched 3 times in the recovery tank, demonstrating an effective oil concentration. Economic analysis confirmed that energy costs were significantly lower than the value of recovered palm oil, highlighting CMB flotation’s cost-effectiveness. The findings support CMB flotation as a scalable and sustainable POME treatment method, with a potential for further efficiency improvements.